2004
DOI: 10.1203/01.pdr.0000099772.66376.02
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Oxygen Fluctuations Produce Less Severe Retinopathy than Hyperoxic Fluctuations in a Rat Model of Retinopathy of Prematurity

Abstract: The aim of this study was to investigate whether the mean around which arterial oxygen fluctuations take place was important in a unique animal model of oxygen-induced retinopathy. Retinopathy of prematurity (ROP) is associated with fluctuating arterial oxygen. A recent retrospective study suggested that management of high-risk preterm infants at lower oxygen saturations was associated with less severe ROP. Rat pups were raised in a variable oxygen environment around a high (24%), normal (21%) or low (17%) mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 30 publications
1
27
0
1
Order By: Relevance
“…Epidemiological studies and case series suggest that high oxygen tensions or saturations and increased variability of oxygenation may be harmful2 22 and that limiting these exposures may be associated with improved outcomes 4 5. The differences in oxygen tension variability observed in this study were large enough to be relevant to the risk of developing retinopathy of prematurity 2 5. Using only saturation monitoring as the basis for administering oxygen might not be the most effective clinical strategy.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Epidemiological studies and case series suggest that high oxygen tensions or saturations and increased variability of oxygenation may be harmful2 22 and that limiting these exposures may be associated with improved outcomes 4 5. The differences in oxygen tension variability observed in this study were large enough to be relevant to the risk of developing retinopathy of prematurity 2 5. Using only saturation monitoring as the basis for administering oxygen might not be the most effective clinical strategy.…”
Section: Discussionmentioning
confidence: 80%
“…Hyperoxia and variability of oxygenation have been linked with increased risk of morbidity in preterm infants 15. Oxygen saturation (Sp o 2 ) and transcutaneous oxygen tension (TcP o 2 ) monitors are used to monitor oxygen levels in preterm infants.…”
mentioning
confidence: 99%
“…Exposure to alternating hypoxia and hyperoxia causes severe proliferative retinopathy in the newborn rat, 18 and also when fluctuations occur at a relatively high level. 19 In animal models, both extreme fluctuations on an hourly basis and smaller but frequent swings as observed in the nursery, produced retinopathy. 20 One study measuring transcutaneous pO 2 showed that severe ROP was associated with greater oxygen tension variability in the first 2 weeks of life.…”
Section: Introductionmentioning
confidence: 99%
“…16 It was observed in animal studies on rat pups that fluctuations of inspired oxygen around higher fractional inspired oxygen levels (mean 24%) lead to more severe vascular abnormalities than around lower fractional inspired oxygen levels (means of 21% and 17%). 17 Oxygen and the brain The effects of oxygen on the brain may be, to some extent, similar to its effect on the retina, as the retina is a specialised part of the central nervous system and thus may share the same pathophysiological processes; cerebral and retinal damage have been suggested to share a common vasoreactive vascular origin. 18 The effect of exposure to pure oxygen on the brain was described as early as in 1959 by Gyllensten,19 who reported that rearing mice in pure oxygen for 20-30 days had a marked deleterious effect on subsequent cortical vascularisation and cellular differentiation.…”
Section: Oxygen and Neonatal Morbidities In A Preterm Infantmentioning
confidence: 99%